The Exports in the Mexican Aerospace Industry in the Context of Covid-19. A Multiple Econometric Regression Analysis - Castillo-Rodríguez, Jesús (2024)
Derived from the health and economic crisis of Covid-19, the aerospace equipment production chains have been severely affected. Consequently, there was a drop in the level of exports of this industry. The objective of this research is to analyze the reference trade balance for aircraft and their parts to calculate the impact that Covid-19 had on the balance of this account. The proposed methodology is through the use of a multiple econometric regression with Dummy variables to capture the effect of the pandemic. The preliminary results show a growth rate in the balance of the trade balance of aerospace equipment to later have a considerable drop of this balance during the development of the pandemic.